SNHG5/miR-299-5p/ATF2 Axis as a Biomarker in Immune Microenvironment of Intervertebral Disc Degeneration - Shi, Yu; Guo, Rong; Zeng, Yanyan; Fang, Qian; Wang, Xianglong; Liu, Wei; Huang, Guozhi; Wu, Wen (Mediators of Inflammation, 2022)
Background and Objective. Intervertebral disc degeneration (IDD) is closely related to back pain. Finding biomarkers of IDD is very helpful for maintaining the function of the intervertebral disc and reducing the occurrence of back pain. This study is to explore the biomarkers in IDD and to explore the role of immune cell infiltration in IDD. Methods. The data sets of GSE56081 and GSE63492 in the Gene Expression Omnibus (GEO) database were used for screening and analysis, and the key gene markers were verified by GSE34095 and GSE126883. Finally, the infiltration of immune cells in the data were analyzed by MCPcounter analysis package. Results. In this study, a ceRNA containing 15 lncRNAs, 9 miRNAs, and 103 mRNAs was constructed. After multimodel screening and verification, key gene marker was found, namely, ATF2. The lncRNA/miRNA/mRNA axis closely related to ATF2 have also been found, namely, SNHG5/miR-299-5p/ATF2. In the analysis of immune infiltration, ATF2 was negatively correlated with T cells but positively correlated with neutrophils and endothelial cells. Conclusion. The SNHG5/miR-299-5p/ATF2 can be used as biomarker of IDD, and infiltration of immune cells plays an important role in the pathological development of IDD. In addition, as a marker of IDD, the involvement of the above-mentioned axis in the pathological development of IDD remains to be further explored.